The interdependence of managerial capabilities toward investment decisions of manufacturing companies on IDX period 2014-2016 - Yunanto, Yogi; Suhariadi, Fendy; Yulianti, Praptini (BISMA (Bisnis dan Manajemen), 2020)
Following the opening of the ASEAN Economic Community (AEC), Indonesian companies must have a reliable manager to benefit from the existence of this AEC. This research aims to explain the effect of managerial ability on investment decisions. Therefore, the dependent variable in this study is the company’s fixed-asset investment decision, while the independent variable is the managerial ability to improve the efficiency of company resources. The sample of this study is go-public manufacturing companies in 2011-2016. This study uses multiple linear analysis techniques such as data envelopment analysis with a banxia frontier analyst as an analysis tool. The results showed managerial ability harmed the investment decision that reflected by the company’s fixed assets improvement.